Social Media and News: Content Bundling and News Quality - de Cornière, Alexandre; Sarvary, Miklos (Management Science, 2023)
The growing influence of internet platforms acting as content aggregators is one of the most important challenges facing the media industry. We develop a simple model to understand the impact of third-party content bundling by a social platform that has a monopoly on showing user-generated content to consumers. In our model, consumers can access news either directly through a newspaper’s website or indirectly through a platform, which also offers social content. We show that content bundling, when unilaterally implemented by the platform, tends to harm publishers and to increase the dispersion of quality across outlets, with initially high-quality outlets investing more and low-quality ones investing less. With many heterogenous newspapers, the result is robust even if each newspaper can prevent the platform from using its content. When content bundling follows an agreement between the platform and publisher, its effects are reversed, as publishers’ profits go up while quality dispersion goes down. In a setup with heterogeneous consumers, we also show that the platform’s ability to personalize the mix of content it shows to users induces publishers to invest more in the quality of their content. This paper was accepted by Dmitri Kuksov, marketing. Funding: The authors thank the Net Institute for financial support. A. de Cornière acknowledges funding from Agence Nationale de la Recherche [Grant ANR-17-EUR-0010 (Investissements d'Avenir Program)], the Toulouse School of Economics Digital Center, and the Artificial and Natural Intelligence Toulouse Institute. Supplemental Material: The online appendix is available at https://doi.org/10.1287/mnsc.2022.4341 .